Identificación de las principales enfermedades en el cultivo de aguacate (Persea americana) en la finca Uyama Farms, cantón Mira - Bastidas Mora, Washington Patricio (2019)
SUMMARY The lack of knowledge of phytosanitary management in avocado cultivation generates large economic losses and affects crop production. This is why the present investigation was carried out in order to identify the main diseases of the Uyama farm, canton Mira, as it is one of the most economically important crops in the parish. The methodology that was used to carry out the research topic was through a survey of thirty farmers of the parish with specific questions addressed to the subject of study. It was determined that the most severe diseases within the avocado crop were root rot, (Phytophthora cinnamomi), followed by the (Cercospora purpurea), angular spot of the fruit, Roña (Sphaceloma perseae), In addition, it is recommended to perform a control of diseases of the avocado crop taking into account the rotation of active ingredients, to avoid economic losses and decrease the resistance of diseases in the avocado crop. Keywords: Identification of diseases, active ingredients, avocado and farm.